Dispositional Optimism in Cardiac Patients and Their Spouses: Dyadic Relations to Well-being and Positive Affect - Karademas, Evangelos; Thomadakis, Christoforos (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The aim of this prospective study was to examine the relation of a positive personal characteristic, i.e., dispositional optimism, to physical and emotional well-being and positive affect in a sample of chronic cardiac patients and their partners. One hundred and four cardiac patients (25 women; mean age = 64.36 years) and their spouses (mean age = 60.04; all couples were married) participated in the study. Patient and partner dispositional optimism was assessed at baseline; well-being and positive affect, four months later. Τhe Actor-Partner Interdependence Model was used to examine the dyadic effects of optimism on physical and emotional well-being and positive affect. Structural equation modeling (SEM) was applied to run these analyses. In almost all cases, patient and spouse baseline optimism was positively related to their own well-being and positive emotions. Furthermore, patient optimism positively predicted spouse outcomes. However, spouse optimism was not related to any of the patients’ indicators of well-being or positive emotions. These findings provide further support to the beneficial role of optimism, at an intra- and also inter-personal level. Furthermore, they indicate that, even when dealing with severe chronic disease, there are still positive personal characteristics, like dispositional optimism, which may help patients and their partners achieve better adaptation and higher levels of well-being.